Human toxocariasis: epidemiology, clinical and laboratory aspects - Breña Chávez, Judith P. (2024)
Toxocariasis is an infection caused by nematode larvae from Toxocara genus, and the most important infective agents for humans are Toxocara canis and Toxocara cati, parasites from dogs and cats, respectively. Toxocara species belong to Ascaridida order, Ascaridodea super-family, Toxocaridae family. The disease in humans is mainly caused by T. canis. Human toxocariasis was described for the .rst time by Wilder in 1950, who identi.ed a then-unknown nematode in a child presenting with a granulomatous lesion in one of his eyes. In 1952, Beaver reported cases of a multi-systemic, chronic, and sever disease, associated to hypereosinophilia. In Peru, in 1991, Maguiña et al. reported the very.rst cases of visceral larva migrans, and in 1999, Miranda et al. reported the very .rst cases of ocular larva migrans.